Antibacterial treatment of bacterial vaginosis: current and emerging therapies - Menard JP (Dove Medical Press, 2011)
Jean-Pierre MenardPôle Enfance et Famille, Conseil Général du Val-de-Marne, Créteil, FranceAbstract: Bacterial vaginosis is a common cause of malodorous vaginal discharge. It is also associated with sexually transmitted infections and adverse pregnancy outcomes. The magnitude of the gynecological and obstetrical consequences has stimulated therapeutic research and led to the testing of several therapies. The objective of this work is to present the currently available therapeutic strategies for the treatment of bacterial vaginosis and associated recommendations, and discuss the emerging therapies.Keywords: bacterial vaginosis, treatment, emerging therapy